The Ecological Problems and Possible Solutions of Beekeeping in Hills and Terai of Chitwan, Nepal - Pokhrel, Suroj (Journal of Agriculture and Environment, 2009)
A general survey accomplished in hills and terai of Chitwan, Nepal in 2004 with an objective to investigate the ecological problems of bee keeping in chitwan and to recommend solutions for its improvement. The survey identifies predators, parasites, diseases, pesticide poisoning, and bee pasture as the key ecological problems in the Hills. Simultaneously, deforestation and pesticide poisoning are the concerned ecological problems in Terai. A very high majority of beekeepers in hills and more than half in Terai faced colony absconding problem in Chitwan. The general survey realized on the need of a special package of program to over come these problems, which include advanced apicultural research and educational activities for the commercialization of beekeeping and advance level crop pollination management in Nepal. For this a clear-cut beekeeping policy and guideline should be developed andshould be implemented. Key words: ecological, absconding, colony status, productivity, species specific The Journal of Agriculture and Environment Vol:9, Jun.2008 Page: 23-33